2020
DOI: 10.9744/jti.22.2.103-110
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Human Behavior and Safety Measure into Evacuation Route Planning in a Volcanic Crisis

Abstract: Many traditional methods in evacuation route planning are motivated by the operational objective, such as total travel/clearance time. Little attention has been given to the human factor and the safety aspect of the evacuees during the planning phase. Our study aims to propose a simple yet practical route planning method that simultaneously considers human behavior, safety factor, and the travel time in a volcanic crisis context. The planning model is developed based on the shortest-path problem with a joint-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…12 of 2012, International Standardization Organization (ISO) 45001:2018 and Australian Standard/New Zealand Standard AS/NZS 4360. Safety studies can uncover stakeholders' knowledge, attitudes, and behaviors, an understanding of which is critical for developing effective OHS interventions [20] [21]. However, the literature shows limited data about research that revealed the risk assessment in fish meatball industries in Indonesia to explore views regarding safety conditions at the workplace, which can be a decisive factor in preventing fatalities, injuries, and illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…12 of 2012, International Standardization Organization (ISO) 45001:2018 and Australian Standard/New Zealand Standard AS/NZS 4360. Safety studies can uncover stakeholders' knowledge, attitudes, and behaviors, an understanding of which is critical for developing effective OHS interventions [20] [21]. However, the literature shows limited data about research that revealed the risk assessment in fish meatball industries in Indonesia to explore views regarding safety conditions at the workplace, which can be a decisive factor in preventing fatalities, injuries, and illnesses.…”
Section: Introductionmentioning
confidence: 99%